2019
DOI: 10.1016/j.eplepsyres.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Resting state functional connectivity patterns associated with pharmacological treatment resistance in temporal lobe epilepsy

Abstract: There are no functional imaging based biomarkers for pharmacological treatment response in temporal lobe epilepsy (TLE). In this study, we investigated whether there is an association between resting state functional brain connectivity (RsFC) and seizure control in TLE. We screened a large database containing resting state functional magnetic resonance imaging (Rs-fMRI) data from 286 epilepsy patients. Patient medical records were screened for seizure characterization, EEG reports for lateralization and locati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
1
24
1
Order By: Relevance
“…There are emerging research studies to introduce the alterations of brain network in epilepsy into clinical practice, such as seizure localization [20,21], surgical outcome prediction [22], neuropsychological implications [6,23], and association with medical outcomes [9,10,24]. There are several reports in line with our present study.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…There are emerging research studies to introduce the alterations of brain network in epilepsy into clinical practice, such as seizure localization [20,21], surgical outcome prediction [22], neuropsychological implications [6,23], and association with medical outcomes [9,10,24]. There are several reports in line with our present study.…”
Section: Discussionsupporting
confidence: 85%
“…They found that patients with drug-resistant epilepsy (DRE) had more widespread gray matter atrophy compared with patients with drug-controlled epilepsy (DCE). A recent study using rs-fMRI demonstrated that healthy controls and patients with DCE showed similar functional connectivity patterns, whereas patients with DRE exhibited a significant bilateral decrease in thalamohippocampal functional connectivity [9]. Another study using rs-fMRI also showed significance for longer paths and reduced local efficiency within the default mode network of patients with DCE compared with those with DRE [10].…”
Section: Introductionmentioning
confidence: 97%
“…Further, diverse changes in neural network connectivity have also been described in response to various treatments in focal epilepsy. Studies have identified regions showing altered connectivity between patients with well-controlled epilepsy and those with treatment-resistant epilepsy (20,21). In this study, all included patients were medically refractory.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that connectivity to the contralateral TL is associated with seizure outcome 32 . Several studies have also shown that subcortical connectivity, namely thalamocortical connectivity, could predict seizure outcome in TL epilepsy 20,33 . One challenge to these studies is that the collinearity between TL+ epilepsy and seizure outcome was not considered.…”
Section: Discussionmentioning
confidence: 99%